Development of Online Web “Ayo Dolanan” as a Media for Preserving Traditional Games For Gen Z in Semarang City - Javier, Mochammad Alban; Wahyudi, Agung (Indonesian Journal of Sport Management, 2024)
Technology development has greatly affected the fading of traditional games in people's lives. Especially with the existence of modern games that are increasingly sophisticated and interesting, traditional games lose prestige. The research aims to develop a traditional game preservation media in the form of online media, which was originally a threat, to be used as a preservation media with the creation of this "Ayo Dolanan" web. The research uses the ADDIE model RND development method which consists of 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The data collection techniques used in the assessment stage are validation sheets from traditional game experts, online media experts, and questionnaires for the people of Semarang City as the initial and final steps, namely analyzing the needs and responses of 156 samples, and the last is the Pre-Test and Post-Test to 30 samples. The results of the developed product have met the feasibility and qualifications as a traditional game preservation media. This can be seen from the results of content validation and product effectiveness by experts: (1) Traditional game experts get an average percentage of 94%, (2) Online media experts get an average percentage of 96%, (3) The significance value of the T-Test (2-tailed) test gets> 0.5 which is equal to 0.000, and (4) The N-Gain test gets an average difference> 0.7 which is equal to 0.7281. So it is concluded that the product "Ayo Dolanan" as a medium for preserving traditional games is "Very Feasible" to use.